Karakteristik penderita epilepsi di RSUD. Dr. H. Abdul Moeloek - Panji Setyawan, Panji; Fitriyani, Fitriyani; Sudiadnyan, Ni Putu Sudiadnyan (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Ikatan Dokter Indonesia (IDI), 2025)
Background: Epilepsy is a chronic neurological disorder affecting the brain, characterized by seizures that may occur partially or generally, often accompanied by loss of consciousness and disruption of other bodily functions. According to the World Health Organization (WHO), approximately 50 million people worldwide suffer from epilepsy, with around 80% living in low- and middle-income countries. Purpose: To determine the characteristics of epilepsy patients at Dr. H. Abdul Moeloek General Hospital. Method: A descriptive quantitative design with secondary data obtained from medical records. The sampling technique used was total sampling, including all epilepsy patients recorded within the study period. Results: The majority of patients had generalized epilepsy (58.3%), most were in the children age group (42.8%), and the dominant gender was male (59.4%). Most patients had primary education (85.6%) and were unemployed (84.5%). The most common treatment duration was three years (55.1%), with generalized seizures being the most frequent type (57.8%). Conclusion: Combination drug therapy was the most widely used, and the majority of epilepsy cases were controlled. Keywords: Epilepsy; Patient Characteristics; Seizure. Pendahuluan: Epilepsi merupakan gangguan neurologis kronis pada otak yang ditandai dengan kejang, baik parsial maupun umum, serta dapat disertai hilangnya kesadaran dan gangguan fungsi tubuh lainnya. Berdasarkan data WHO, sekitar 50 juta orang di dunia menderita epilepsi, dengan 80% di antaranya berada di negara berpendapatan rendah dan menengah. Tujuan: Untuk mengetahui karakteristik penderita epilepsi di RSUD Dr. H. Abdul Moeloek. Metode: Deskriptif kuantitatif dengan data sekunder dari rekam medik, dan teknik pengambilan sampel dilakukan secara total sampling. Hasil: Sebagian besar pasien mengalami epilepsi jenis umum (58.3%), usia terbanyak adalah anak-anak (42.8%), dan mayoritas berjenis kelamin laki-laki (59.4%). Tingkat pendidikan terbanyak adalah pendidikan dasar (85.6%) dengan status pekerjaan sebagian besar tidak bekerja (84.5%). Durasi pengobatan terbanyak adalah 3 tahun (55.1%), jenis bangkitan terbanyak adalah bangkitan umum (57.8%), serta terapi yang paling banyak digunakan adalah kombinasi obat (75.9%). Simpulan: Terapi obat kombinasi adalah yang paling banyak digunakan, dan mayoritas kasus epilepsi terkontrol. Kata Kunci: Epilepsi; Karakteristik Pasien; Kejang.